Do parliaments underrepresent women's policy preferences? Exploring gender equality in policy congruence in 21 European democracies. Issue 2 (1st February 2019) - Dingler, Sarah C.; Kroeber, Corinna; Fortin-Rittberger, Jessica
ABSTRACT: Although there are considerably more men than women in most parliaments around the world, we know little about whether male-dominated legislatures neglect women's policy preferences. Our article addresses this gap by analysing the congruence of policy preferences between women, men and their elected representatives. We endeavour to answer two questions. Are women's policy preferences underrepresented in modern democracies? If so, which factors explain the size of the gender gaps in policy preference congruence? Comparing 21 European countries, we show that women's preferences actually tend to be more accurately represented in parliaments than those of men. Moreover, our analyses reveal that this unanticipated finding is not driven by the share of female office-holders, but rather by levels of women's turnout, which leads us to conclude that who votes is more important than who represents for policy preference congruence.